2011
DOI: 10.3844/ajavsp.2011.88.92
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gestation and Maternal Copper on the Fetal Fluids and Tissues Copper Concentrations in Sheep

Abstract: Problem statement: Samples of allantoic, amniotic fluid, fetal liver, kidney, maternal plasma and liver were collected from 30 ewes and classified into either early or late gestation and copper concentrations were measured. Approach: The Cu concentrations in the maternal plasma, allantoic, amniotic fluid, fetal liver and kidney increased significantly (p<0.01) during late gestation while maternal liver Cu decreased significantly (p<0.01). Results: Significant positive relationships were recorded between age of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Whilst dam liver Cu concentration decreases significantly from trimester one through two to three, foetal liver Cu concentration increases significantly throughout gestation in cattle (Gooneratne & Christensen 1989a) and pigs (Richards 1999), but the rate of accumulation in the foetus and depletion in the dam depends on the availability of Cu from the diet (Gooneratne et al 1986a). In addition, the weight of the foetal liver increases significantly from about 7-mo gestation, which in combination with the significant increase in liver Cu concentration at that time results in a substantial increase in the total Cu accretion in the foetal liver (Graham et al 1994) at the expense of the maternal pool in cattle (Gooneratne, Laarveld & Christensen, unpublished observations) and sheep (Hefnawy et al 2011). If only the liver Cu concentrations and its accretion at different stages of gestation are considered, quantitative accretion may fail to be detected, particularly at times of rapid foetus and foetal liver growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst dam liver Cu concentration decreases significantly from trimester one through two to three, foetal liver Cu concentration increases significantly throughout gestation in cattle (Gooneratne & Christensen 1989a) and pigs (Richards 1999), but the rate of accumulation in the foetus and depletion in the dam depends on the availability of Cu from the diet (Gooneratne et al 1986a). In addition, the weight of the foetal liver increases significantly from about 7-mo gestation, which in combination with the significant increase in liver Cu concentration at that time results in a substantial increase in the total Cu accretion in the foetal liver (Graham et al 1994) at the expense of the maternal pool in cattle (Gooneratne, Laarveld & Christensen, unpublished observations) and sheep (Hefnawy et al 2011). If only the liver Cu concentrations and its accretion at different stages of gestation are considered, quantitative accretion may fail to be detected, particularly at times of rapid foetus and foetal liver growth.…”
Section: Discussionmentioning
confidence: 99%
“…Homeostasis of these two essential trace minerals in the pregnant animal depends on the relative absorption, excretion and their transfer to the foetus (Gooneratne, Buckley & Christensen 1989). High Cu content in most new-born animals suggests placental transfer and foetal liver storage before birth (Cunningham 1931;Gooneratne 1986;Gooneratne & Christensen 1989a, 1989bHefnawy et al 2011;Pryor 1964) with foetal liver Cu concentration as high as 50% in the human foetus (Widdowson 1974). Early work indicated that bile is the major excretory route for many trace minerals (Evans 1973) and 94% of the excreted Cu is via faeces (Moss et al 1974).…”
Section: Introductionmentioning
confidence: 99%